PROPIEDADES ELECTRÓNICAS DE SISTEMAS TIPO PANAL DE ABEJAS EN DOS DIMENSIONES. UN ESTUDIO AB INITIO - Rojas-Cuervo, Ángela M.; Fonseca-Romero, Karen M.; Rey-González, Rafael R. (MOMENTO, 2015)
The novel properties of graphene have motivated the search for materials with similar characteristics. In this work, we study the chemical stability and the band structures of GaAs and GaN hexagonal monolayers, using a first principles formalism. Results obtained with SIESTA code, as a DFT implementation, show GaAs (GaN) is an indirect (a direct) bandgap semiconductor.